Moxifloxacin and Sitafloxacin Treatment Failure in Mycoplasma genitalium Infection: Association with parC Mutation G248T (S83I) and Concurrent gyrA Mutations. (22nd October 2019) - Murray, Gerald L; Bodiyabadu, Kaveesha; Danielewski, Jennifer; Garland, Suzanne M; Machalek, Dorothy A; Fairley, Christopher K; Jensen, Jørgen S; Williamson, Deborah A; Tan, Lit Y; Mokany, Elisa; Durukan, Duygu; Bradshaw, Catriona S
Abstract: Background: The basis of fluoroquinolone treatment failure for Mycoplasma genitalium is poorly understood. Methods: To identify mutations associated with failure we sequenced key regions of the M. genitalium parC and gyrA genes for patients undergoing sequential therapy with doxycycline-moxifloxacin (201 patients, including 21 with failure) or doxycycline-sitafloxacin (126 patients, including 13 with failure). Results: The parC G248T/S83I mutation was more common among patients with failed sequential doxycycline-moxifloxacin (present in 76.2% of failures vs 7.8% cures, P < .001) or doxycycline-sitafloxacin (50% vs 16.8%, respectively; P = .01) treatment. Doxycycline-sitafloxacin was more efficacious than doxycycline-moxifloxacin against infections carrying the parC mutation conferring S83I amino acid change. Treatment was more likely to fail in these infections if they had a concurrent gyrA mutation (M95I or D99N) (P = .07 for doxycycline-moxifloxacin group and P = .009 for doxycycline-sitafloxacin group), suggesting an additive effect. Conclusions: This study indicates that parC G248T/S83I mutations contribute to failure of moxifloxacin and sitafloxacin, and the findings will inform the development of quinolone resistance assays needed to ensure optimal selection of antimicrobials for M. genitalium. Abstract : For patients undergoing sequential doxycycline-fluoroquinolone therapy for Mycoplasma genitalium, the parC S83I mutation was significantly associated with both moxifloxacin and sitafloxacin failure. Those with concurrent parC S83I and gyrA M95 or D99 mutations were more likely to have sitafloxacin failure.